2013
DOI: 10.1128/aac.00659-13
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-3,3′-Digallate and Lactic Acid Combinations Reduce Herpes Simplex Virus Infectivity

Abstract: The present study examined the efficacy of using multiple mechanisms as part of a topical microbicide to inactivate herpes simplex virus (HSV) by combining theaflavin-3,3=-digallate (TF-3) and lactic acid (LA) over the pH range of 4.0 to 5.7 to mimic conditions in the female reproductive tract. Six clinical isolates of HSV-2 and two clinical isolates of HSV-1 were almost completely inactivated when TF-3 (100 M) was present with LA over the pH range of 4.5 to 5.7, whereas four additional HSV-1 clinical isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
(56 reference statements)
1
24
0
Order By: Relevance
“…This high stability allows it to be a suitable topical antiviral agent in vaginal pH (Jhoo et al, 2005). In addition, a recent study has shown that the combination of TF3 and lactic acid may be an effective way to inactivate HSV in the vaginal area, confirming the results seen here (Isaacs and Xu, 2013). Finally, the current market anti-herpetic medications are highly costly, making TF3 a plausible, affordable solution for treatment and prevention of HSV infections.…”
Section: Discussionsupporting
confidence: 69%
“…This high stability allows it to be a suitable topical antiviral agent in vaginal pH (Jhoo et al, 2005). In addition, a recent study has shown that the combination of TF3 and lactic acid may be an effective way to inactivate HSV in the vaginal area, confirming the results seen here (Isaacs and Xu, 2013). Finally, the current market anti-herpetic medications are highly costly, making TF3 a plausible, affordable solution for treatment and prevention of HSV infections.…”
Section: Discussionsupporting
confidence: 69%
“…TF-3 is considered to have many health benefits, such as, it reduces risk of coronary heart disease, viral infection and prevention of cancer [217, 218]. …”
Section: Pkc Modulation By Polyphenolsmentioning
confidence: 99%
“…; Aldunate et al . ; Isaacs & Xu, , ). Lactic acid also inactivates a broad range of BV‐associated microbes at pH < 4.5 (O'Hanlon et al .…”
Section: Introductionmentioning
confidence: 99%